Fiber contribution on elastic properties of cellulose composites: A multiscale numerical study. Issue 3 (10th January 2022) - Yasuda, Shogai; Teramoto, Yoshikuni; Ogoe, Shinji; Uetsuji, Yasutomo
Abstract: Multiscale finite element analysis based on the asymptotic homogenization theory was carried out for short fiber reinforced plastics (FRP), and the effects of fiber morphologies on mechanical properties were systematically organized. Cellulose microfibers were used as the reinforcing fibers and polypropylene was used as the matrix. In order to quantify the enhancement effect of intrinsic fibers on the mechanical properties, a new indicator based on strain energy, contribution proportion of fiber (CP f ) was proposed. In this paper, as the first demonstration of introducing the CP f, unidirectionally oriented short FRP was focused and elastic properties were analyzed for fundamental fiber morphologies. In terms of the fluctuation rate based on the elastic modulus of the matrix, when the volume content of fiber is 3.0 vol%, the elastic modulus of composites varied by 106%, 105%, 97.6%, and 35.1%, respectively, depending on the fiber orientation, fiber aspect ratio, fiber/matrix interface and fiber‐to‐fiber distance. Based on the CP f, fiber morphologies could be divided into two. The first factors are fiber orientation angle and fiber content, which determine the rate of change in mechanical properties with respect to the CP f . The second factors are fiber aspect ratio, fiber/matrix interface, and fiber‐to‐fiber distance, which affect the mechanical properties according to the rate of change determined by the first factors. The complicated influence of the fiber morphologies on the mechanical properties could be unified by introducing the CP f . These computations show that CP f is effective for systematic analysis and design of fiber morphologies. Abstract : Fiber morphologies could be divided into two factors based on the proposed fiber contribution proportion (CP f ). The first factors are fiber orientation angle and fiber content, which determine the rate of change in mechanical properties with respect to the CP f, and the second factors are fiber aspect ratio, interface, and fiber distance, which affect the mechanical properties according to the rate of change determined by the first factors.